GRAHAM GREENE'S “THE HEART OF THE MATTER” AND ITS IMPACT ON THE SPIRITUALITY OF THE YOUTH OF THE ERA - Marifatkhon Boltabayeva (Bright Mind Publishing, 2026)
This article examines the spiritual and moral impact of the novel This Battlefield, its emergence and public presentation, criticism from writers, and the impact of the love triangle.
Keywords: In the spirit of success, gender reassignment, life trajectory, submissive figure, communist, panorama, postmodern love triangle, saint, tangled webs, liberal soviet researchers.